P17.35 Cost-effectiveness analysis of abacavir-based and tenofovir-based regimens in singapore. (13th September 2015) - Ong, YY; Hoo, G; Law, HL; Ng, OT
Abstract : Introduction: Human immunodeficiency virus (HIV) infection has evolved into a chronic disease with the use of highly active antiretroviral therapy (HAART). As survival rates improve and the duration of treatment increases, cost of treatment will be a major factor affecting the choice of HAART. Objective: To assess the cost-effectiveness of abacavir-based and tenofovir-based regimens in Singapore. Methods: This was a single-centre, retrospective study. Data was obtained from online medical records and hardcopy case files. HIV-positive patients on each regimen were matched according to age group, gender, race, body mass index and HAART. An incremental cost-effectiveness ratio (ICER) analysis was performed to evaluate the cost-effectiveness between abacavir (ABC)-based and tenofovir (TDF)-based regimens between the evaluation period of week 12 to 36 and week 37 to week 60. Costs were reported in Singapore dollars (S). Results: Two hundred and thirty patients were analysed (82.2% Chinese, 91.3% male, age: 46.0 ± 13.0 years old), 115 patients in each group. The most common used combinations were ABC, lamivudine (3TC) and efavirenz (EFV) (76.5%), and TDF, 3TC and EFV (78.2%); followed by ABC, 3TC, boosted atazanavir (ATV/r) (13.0%), and TDF, 3TC and ATV/r (11.3%). Majority of the patients in each arm were at least 95% adherent to their medication regimens (93.0% and 91.3% for ABC and TDF group respectively). For both evaluation periods, more patients in ABC group obtained undetectable viral load (77.4% vs 59.1% and 81.7% vs 76.5%). The ICER value was –S13348.72 for the period of week 12 to 36 and –S19085.37 for the period of week 37 to week 60. Conclusion: ABC-based regimen was found to be more cost-effective than TDF-based regimen with similar virologic control rates in HIV patients in Singapore. This can translate to public healthcare cost savings in the near future.